Distant voices still heard contemporary readings of French Renaissance literature - O'Brien, John 1954-; Quainton, Malcolm (Liverpool University Press, 2000)
This book seeks to satisfy a pedagogical need. It is designed for the new graduate student in England and elsewhere, although it may profitably be used by the enterprising final year undergraduate. Its aim is to introduce the modern student to readings of French Renaissance literature, drawing on the perspectives of contemporary literary theories. The volume is organised by paired readings of five major sixteenth-century French writers, with interpretations covering, among others, structuralism, semiotics, feminism and psychoanalysis. Linking these interpretations is a constant interest in problems such as the role of the reader, the nature of the text and the question of gender. The Introduction contextualises the encounter between literary theory and Renaissance texts by using the contributions as pivotal points in the development of critical thinking about this period in early modern literature. All foreign language quotations are translated into English, and the book is intended to be of practical interest to a wide range of readers, from modern linguists to those studying critical theory, comparative literature or cultural history
Title from publisher's bibliographic system (viewed on 07 Jul 2017)
Keywords: Geschichte 1500-1600; French literature / 16th century / History and criticism